Inter-limb coordination during sprint acceleration - Bayne, H.; Donaldson, B.; Bezodis, N. (ISBS Proceedings Archive (Michigan), 2020)
Bilateral coordination is inherent to running motions but has not been investigated during sprint acceleration. The purpose of the study was to examine inter-limb thigh coordination during the first four steps of sprint acceleration in elite and sub-elite athletes. Anti-phase coordination patterns predominated in each step, but the proportion of anti-phase motion was higher in elite athletes (85.9 ± 10.8%) than sub-elite athletes (76.8 ± 10.9%, ES 0.83). Coordination profiles suggest that sub-elite athletes exhibit longer periods of the trailing (+) pattern around the time of touchdown (swing thigh flexing, stance thigh fixed) and the leading (-) pattern in the latter part of stance (stance thigh extending, swing thigh fixed) compared with elite athletes. These results provide preliminary empirical support for the emphasis placed on the switching of the limbs by coaches.